Room sterilization program using a remote-controlled disinfectant robot at Masjid Agung, Central Java - Arifin, Zaenal; Heryanto, M. Ary; Tamamy, Aries Jehan; Pamungkas, Hery; Karampung, Felix Etena Orba; Hafaz, Mohamad; Gunawan, Wahyu Sahrul (Community Empowerment, 2021)
One of the causes of people being exposed to the Covid-19 virus is the spread of the virus through the air. To prevent this, it is necessary to sterilize so that the virus in the air can be neutralized. One of the technologies that can be used to disinfect the air so that the air is free from the Covid-19 virus is Ultra Violet (UV) light. UV rays have radiation that is quite harsh, so when exposed to human skin continuously can cause damage to skin tissue. The service team developed a remote-control robot that can replace humans to carry out the disinfection process in a room by utilizing UV light. The area where congregational prayers were held at the Masjid Agung, Central Java (MAJT) visited by no less than 100 people every day. The robot was effectively able to operate well in the disinfectant process. This phase 1 prototype has a height of 48 cm and expected to be developed again so that it can reach higher places and can reduce the risk of spreading the Covid-19 virus.